(untitled) ("Journal "U". Economy. Management. Finance.", 2019)
The article reveals the essence of the concept of interbank lending market. The main indicators of the state of the interbank credit market in the Russian Federation are considered. The dynamics of interbank loans granted by the Central Bank of the Russian Federation, the volume of loans and deposits received from other credit institutions in rubles and foreign currency, the volume of money received from resident credit institutions and non-resident credit institutions for 2016-2018 are assessed.